Efektivitas Metode Talaqqi Menghafal Al-Qur’an di MI/SD: Review Jurnal - Khotimah, Maulidy Putri Khusnul; Faliani, Eli; nadlir, Nadlir (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2024)
This study aims to determine the effectiveness of the Talaqqi method in memorizing the Qur'an among students at the MI/elementary school level. This research employs a literature review method with a qualitative approach. The article was written by applying inclusion and exclusion criteria. Based on a search using the keyword "Talaqqi Method" on Portal Garuda within the past 10 years (2015–2024), 140 articles were found. After further filtering using additional keywords such as "Qur'an Memorization" and "MI Students", the number of findings was reduced to 21 articles. From these results, 7 articles were deemed relevant to the research topic. Thus, 7 articles were included in the inclusion criteria, while 133 articles were excluded. Based on the analysis of these seven journals, it was concluded that the Talaqqi method is highly effective in enhancing the ability of MI (Madrasah Ibtidaiyah) and elementary school students to memorize the Qur'an. Through this approach, students can directly imitate the teacher's correct pronunciation, thereby minimizing reading errors. The analysis results show a significant improvement in memorization skills in various studies, whether using quantitative or qualitative approaches. Additionally, the Talaqqi method has positive impacts on non-academic aspects, such as fostering student discipline, responsibility, and patience.